Efektivitas Quantum Learning Tipe Card Sort terhadap Keterampilan Berbicara Bahasa Arab Siswa Kelas IX MTsN 1 Bogor: The Effectiveness of Quantum Learning Card Sort Type on Arabic Speaking Skills of Grade IX Students of MTsN 1 Bogor - Bukhori, Aisyah Afifah; Rahmawati, Nailur (Universitas Negeri Semarang, 2025)
In learning, applying developmentally appropriate methods can increase students' learning enthusiasm and focus because they include activities that refer to students' interests, level of cognitive development and social and emotional maturity. Class IX students at MTs Negeri 1 Bogor have not achieved the learning objectives in speaking skills. One of the factors for this is the lack of application of appropriate methods, resulting in boring learning and students being afraid to face this learning. This can affect students' speaking skills. Therefore, a fun method is needed where students do not feel pressured. The aim of this research is to determine the effectiveness of implementing card sort type quantum learning in learning Arabic speaking skills for class IX students at MTs Negeri 1 Bogor. The type and design of the research is experimental research with a quasi-experimental non-equivalent group design. Data collection techniques in this research used tests and non-tests. For test techniques, the instruments used are questions in the form of oral tests, while for non-test techniques they are interviews, observations, questionnaires and documentation. The data analysis technique used is hypothesis testing (T-test). The results of this research show that the card sort type quantum learning method is effective in improving the Arabic speaking skills of class IX students at MTs Negeri 1 Bogor. This is proven by the control class's average pre-test score of 70.80 and the control class' post-test score of 74.57. Meanwhile, for the experiment, the pre-test average was 65.16 and the post-test average was 75.16. In the data analysis regarding the level of normality test for the two classes, the control class and the experimental class in the pre-test and post-test were normally distributed. Apart from that, the t-test calculation using SPSS version 29 obtained a pre-test and post-test significance value of 0.001, which means significance <0.05. This is also proven by an increase in the average of the pre-test and post-test of the experimental class. This shows that there is an influence of the card sort type quantum learning method on the post-test results of the experimental class. So Ho is rejected and Ha is accepted. Meanwhile, based on the results of closed questionnaires that have been filled out by students, it also proves that students can participate in learning well, focus, and easily understand Arabic language learning in speaking skills using the card sort type quantum learning method.